A new model for the quality of urban places: Integration of objective and subjective indicators using information technologies - Ozbakir, Buket Aysegul (University of Ottawa (Canada), 2006)
Quality of place (QOP) is essential for building a "competitive and livable city" and the competitiveness is determined by the opportunities that the city can provide. Therefore not only physical characteristics of the neighborhoods but also social structure and personal satisfaction about a place are significant in the assessment of QOP. This thesis discusses how to measure the performance of places from different perspectives. Measuring the QOP is a hard task since it involves both objective and subjective dimensions. Most of the research on QOP have focused on either subjective or objective measures and a limited number of efforts have been made in recent years to collect both types of indicators. Hence, the main objective of this research has been to offer a new definition for QOP where both dimensions are integrated and to introduce a new methodology where information technologies such as geographical information systems (GIS) and remote sensing (RS) can be applied to understand the contribution of these two dimensions of QOP. The proposed methodological approach is tested for Montreal as a study case where social, physical and experiential community structural information are analyzed using different sources of data (census, survey, GIS based ancillary data and satellite images). Social structural information is analyzed using census data which help to understand the link between the socio-demographic/economic characteristics and QOP in census tract (CT) at city-wide scale. Then, physical structural information through accessibility to public services and urban land use is analyzed with the help of RS and GIS techniques. In the subjective dimension, survey data are used to explore the experiential community structural information that helps to understand the individual's own perceptions about the QOP where they live. Finally, both of the objective and subjective dimensions are integrated through multi-criteria evaluation (MCE) in a GIS environment. The results indicate that a place may be explained through some objective criteria; however, the situation may be different when the personal evaluations of people living in that area are considered. Thus, the results support that both dimensions are necessary to evaluate the complete picture of QOP. Key words. Quality of Place, Objective and Subjective Dimensions, Community Structures, Remote Sensing, Geographical Information Systems, Transformed Difference Vegetation Index, Spatial Analysis, Principal Component Analysis, Multi-Criteria Evaluation, Montreal.
Keywords: Geography.; Urban and Regional Planning.